Using knowledge to improve development effectiveness : an evaluation of the World Bank economic and sector work and technical assistance, 2000-2006 (Online access: World Bank World Bank Open Knowledge Repository., 2008)
The World Bank has committed itself to becoming a "global knowledge bank", using knowledge to improve the development effectiveness of its work. Two of the analytical and advisory ways the Bank provides knowledge to its client countries are economic and sector work (ESW) and nonlending technical assistance (TA). ESW and TA are an essential part of the Bank's engagement with its clients--it spent 910 million (26% of its spending on country services) on these products during fiscal 2000-06. This evaluation assesses the extent to which the stated objectives of ESW and TA have been met. I